Alterations of Vertical Jump Mechanics after a Half-Marathon Mountain Running Race - Rousanoglou, Elissavet N. (J Sports Sci Med, 2016)
The fatiguing effect of long-distance running has been examined in the context of a variety of parameters. However, there is scarcity of data regarding its effect on the vertical jump mechanics. The purpose of this study was to investigate the alterations of countermovement jump (CMJ) mechanics after a half-marathon mountain race. Twenty-seven runners performed CMJs before the race (Pre), immediately after the race (Post 1) and five minutes after Post 1 (Post 2). Instantaneous and ensemble-average analysis focused on jump height and, the maximum peaks and time-to-maximum peaks of: Displacement, vertical force (Fz), anterior-posterior force (Fx), Velocity and Power, in the eccentric (t(ECC)) and concentric (t(CON)) phase of the jump, respectively. Repeated measures ANOVAs were used for statistical analysis (p ≤ 0.05). The jump height decrease was significant in Post 2 (-7.9%) but not in Post 1 (-4.1%). Fx and Velocity decreased significantly in both Post 1 (only in t(ECC)) and Post 2 (both t(ECC) and t(CON)). Α timing shift of the Fz peaks (earlier during t(ECC) and later during t(CON)) and altered relative peak times (only in t(ECC)) were also observed. Ensemble-average analysis revealed several time intervals of significant post-race alterations and a timing shift in the Fz-Velocity loop. An overall trend of lowered post-race jump output and mechanics was characterised by altered jump timing, restricted anterior-posterior movement and altered force-velocity relations. The specificity of mountain running fatigue to eccentric muscle work, appears to be reflected in the different time order of the post-race reductions, with the eccentric phase reductions preceding those of the concentric one. Thus, those who engage in mountain running should particularly consider downhill training to optimise eccentric muscular action.